Retaining population with water? Irrigation policies and depopulation in Spain over the long term - Ignacio Cazcarro; Miguel Martín-Retortillo; Guillermo Rodríguez-López; Ana Serrano; Javier Silvestre Rodríguez (European Historical Economics Society (EHES), 2024)
Depopulation, especially, but not only, rural, has become a major concern across many countries. As one type of place-based policy, irrigation has been claimed to contribute to resettling populations and reducing outward migration, by increasing agricultural output, productivity, and competitiveness and, consequently, employment and living standards. This paper aims to elucidate on the relationship between irrigation and population for Spain, historically and currently the most irrigated country and one of the most depopulated countries in Europe. We use municipal-level data over the period 1910-2011 and exploit a staggered difference-in-differences design. Overall, we find an effect on population only for irrigation developments that started in the relatively distant past. In any case, effects are temporary or tend to level off. We also consider trade-offs. We discuss the policy implications of the findings in light of current policies, and in terms of environmental and economic costs of increasing the intensity of irrigation.
Keywords: J11; Q15; Q25; R11; N54; N94; 330; Depopulation; place-based policies; irrigation programs; long-term view; staggered DiD; Spain